Limited genetic changes observed during in situ and ex situ conservation in Nordic populations of red clover (Trifolium pratense) - Hagenblad, Jenny; Aloisi, Karolina; Marum, Petter; Öhlund, Linda; Solberg, Svein Øivind; Asdal, Åsmund; Palmé, Anna (Frontiers in Plant Science, 2023)
In situ and ex situ conservation are the two main approaches for preserving genetic diversity. The advantages and disadvantages of the two approaches have been discussed but their genetic effects have not been fully evaluated. In this study we investigate the effects of the two conservation approaches on genetic diversity in red clover. Seed samples collected from wild populations in Sweden and Norway in 1980, their subsequent generations created during seed regeneration at the gene bank and samples recollected from the same location as the original samples, were analyzed with microsatellite markers, alongside reference samples from cultivars. Overall, there was a differentiation between cultivars and the wild material and between wild material from Sweden and Norway. In general, the original collections clustered together with the later generations of the same accession in the gene bank, and with the recollected samples from the same location, and the level of diversity remained the same among samples of the same accession. Limited gene flow from cultivated varieties to the wild populations was detected; however, some wild individuals are likely to be escapees or affected by gene flow. In conclusion, there were examples of genetic changes within individual accessions both in situ and ex situ, as is also to be expected in any living population. However, we observed only limited genetic changes in both in situ and ex situ conservation over the generations included in this study and with the relatively large populations used in the ex situ conservation in the gene bank at NordGen.